CORRELATION-REGRESSION ANALYSIS OF THE IMPACT OF EXPORTS AND IMPORTS ON THE GDP LEVEL OF UKRAINE - AZAROVA, Anzhelika; NIKIFOROVA, Liliіa; RUZAKOVA, Olga; KHYMYCH, Victoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to econometric modeling of the impact of export-import operations on the level of gross domestic product of Ukraine. The paper considers the role of foreign trade in the country's economic growth, determines how changes in the volume of exports and imports affect the economic situation in the state. The analysis allows us to identify key factors that determine the balance between export-import flows, as well as assess their impact on macroeconomic indicators, in particular on GDP growth.The relevance of the study is due to the need to adapt the Ukrainian economy to globalization challenges and strengthen the role of foreign trade in the formation of GDP. The article identifies key problems associated with insufficient research into the role of exports and imports in the country's economy, in particular, assessing the level of dependence of GDP on foreign trade, the problem of multicollinearity in export-import econometric models and a comparative analysis of the impact of imports and exports on the level of gross domestic product of Ukraine.To analyze the impact of exports and imports on the level of gross domestic product, the authors of the article propose to use the method of correlation-regression modeling, which allows us to accurately assess the quantitative impact of the components of the foreign trade balance on economic growth. The paper also takes into account the specifics of the Ukrainian economy, which largely depends on the export of raw materials and the import of high-tech products. Based on the data obtained, a model of the dependence of GDP on exports and imports was built, which allows us to assess their percentage impact in the formation of the country's economic indicators.The results of the study indicate that export-import operations have a positive impact on GDP, ensuring the inflow of foreign exchange resources and creating new opportunities for the development of sectors of the economy and make contributing to the introduction of new technologies and satisfying domestic demand. At the same time, imports can increase dependence on foreign markets.
Keywords: correlation-regression modeling; least squares method; exports; imports; gross domestic product